1991
DOI: 10.2105/ajph.81.3.350
|View full text |Cite
|
Sign up to set email alerts
|

The UCLA population studies of CORD: X. A cohort study of changes in respiratory function associated with chronic exposure to SOx, NOx, and hydrocarbons.

Abstract: Two never-smoking cohorts in Southern California, one in Lancaster (N = 2340) exposed only to moderate levels of oxidants and the other in Long Beach (N = 1326) exposed to high levels of SOx, NO2, hydrocarbons and particulates completed spirometry and the single-breath nitrogen test five to six years apart. Forty-seven percent and 45 percent of the participants were retested. Mean results at baseline for those tested and not retested were similar. Loss to follow-up was primarily due to moving (39 percent and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 39 publications
(2 reference statements)
2
31
0
Order By: Relevance
“…The University of California at Los Angeles Chronic Obstructive Respiratory Disease (UCLA-CORD) study followed changes in lung function over time in several cohorts of smokers and nonsmokers residing in areas of Southern California, chronically exposed to different levels and types of air pollution [72,73]. The three areas were: Lancaster, with moderate levels of photochemical oxidants and low levels of particles; Glendora, with high levels of photochemical oxidants; and Long Beach with high levels of particles, nitrogen oxides and sulphates.…”
Section: Lung Function Decline In Adultsmentioning
confidence: 99%
“…The University of California at Los Angeles Chronic Obstructive Respiratory Disease (UCLA-CORD) study followed changes in lung function over time in several cohorts of smokers and nonsmokers residing in areas of Southern California, chronically exposed to different levels and types of air pollution [72,73]. The three areas were: Lancaster, with moderate levels of photochemical oxidants and low levels of particles; Glendora, with high levels of photochemical oxidants; and Long Beach with high levels of particles, nitrogen oxides and sulphates.…”
Section: Lung Function Decline In Adultsmentioning
confidence: 99%
“…Studies of long-term exposures found decreases in lung function in humans (42,(57)(58)(59) and changes in the respiratory tract in animals (60). The U.S. EPA review of animal tests and epidemiologic studies of ozone (61) concluded that chronic effects may be associated with long-term exposure to ozone.…”
Section: Ozonementioning
confidence: 99%
“…To date, traditional, population-based epidemiologic studies that have tried to address process (e.g., accelerated dedine in lung function) have been restricted to the evaluation of a limited range of lung function measures. They also have been handicapped by a number of problems: a) large losses to follow-up (12,13), which on the surface do not appear to have affected validity; b) inadequate characterization of individual and group exposure to ozone prior to study onset; c) difficulties in obtaining detailed data on concurrent ozone exposure for large numbers of subjects; d ) lack of data on modiying and/or confounding factors; and e) the relatively short duration of follow-up (12,13) or the purely cross-sectional nature of their evaluation (14). These Environmental Health Perspectives Supplements Volume 101, Supplement 4, December 1993 studies have derived their epidemiologic appeal from a perceived need to have study samples from whom generalizations can be made to some population at large.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of controlled exposure studies to identify, unequivocally, asthmatics as a sensitive subpopulation was not seen as limiting in this context, since it may have been the result of a) inadequate exposures used in the controlled exposure studies that have been conducted to date (20), b) the inclusion of only milder asthmatics, c) the exdusion of asthmatics with acute respiratory illness or its exacerbation, and d) failure to simulate the complex mix of air pollutants to which such individuals may be exposed (13). Epidemiologic studies, in conjunction with additional controlled exposure studies (20,21), were considered essential to address the above problems and to identify more clearly other sensitive subgroups and the factors that define sensitivity to ozone.…”
Section: Introductionmentioning
confidence: 99%